Raising Quality of Goods in Internet-Stores and Marketplaces on the Basis of Using Internet-Technologies - O. S. Karashchuk (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies current situation with the quality of goods when they are sold through the Internet and points to key causes of inadequate quality. To identify the most serious violations in product quality the author summarized available publications and gave conclusions of Rospotrebnadzor concerning the problem. The trends of upgrading control over the quality of goods put forward in the article cover systematized recommendations of studies dealing with similar problems and author’s proposals based on using advanced internet-technologies. Special attention in recommended internet-technologies capable of improving control over the quality of goods is given to technologies of big data, AI and Internet of things. The article proposes to use technologies of big data to raise accuracy of product offer to each customer on the basis of individualization of searching for suitable goods by quality with regard to specific characteristics of each customer. Possibility of using AI technology was grounded, in particular, spectral methods and artificial sight during checking the product quality. The author recommend to develop technology of Internet of things, as now it is underdeveloped in order to diagnose and monitor the quality by using pick-ups and specific equipment, which could allow us in the near future to pass to the smart-quality model.